Porphyran From Porphyra haitanensis Alleviates Obesity by Reducing Lipid Accumulation and Modulating gut Microbiota Homeostasis - Wang, Xueliang; Dong, Juqin; Liang, Wei; Fang, Yi; Liang, Meinong; Xu, Lixia; Sun, Wuyang; Li, Xiaoxing (Frontiers in Pharmacology, 2022)
Porphyran possess various activities, while the effects of the porphyran from Porphyra haitanensis (PPH) on obesity are rarely reported. In this study, C57BL/6J male mice were fed with HFD combined with PPH gavage (50 mg/kg/d) for 16 weeks and body weight was measured once a week. Afterthat, serum, adipose and liver tissues were collected for physiological and biochemical analyses. Our research indicated that PPH treatment alleviated obesity in HFD-fed mice. PPH alleviated fat accumulation in serum, liver, and adipose tissues. In addition, PPH activated the AMPK-HSL/ACC pathway in epididymal adipose tissue to reduce the lipid accumulation. Moreover, PPH turned white adipose into brown and activated the PGC 1α-UCP 1-mitochondrial pathway in scapular adipose tissue to generate more heat. Interestingly, PPH regulated the colonic microbiota homeostasis in obese mice, including significantly increased the relative abundance of Roseburia and Eubacterium, while reduced the relative abundance of Helicobacter. Moreover, Spearman's correlation analysis demonstrated that regulation of gut microbiota can decrease lipid accumulation. In summary, our study illustrated that PPH possess the potentiality to be developed as anti-obesity agent.